Pemberdayaan Kelompok Wanita Tani (KWT) Anggrek - Rita Kusumawati (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Women Farmers Group (KWT) is a small community that has a reciprocal relationship in behavior and processes in its environment so that it can become an association or unity. This Program aims to assist partners in the form of empowering members in order to improve the economic welfare of partners. The partner in this service program is the Anggrek Women Farmer Group (KWT), which was founded in 2018 and has 40 members. In its journey, this group faced several problems, namely problems including: the existing cultivation equipment was still very limited, this group did not have its own land, while cultivation was carried out in the yards of KWT members' houses, so that the cultivation yields obtained were still very limited. In the management aspect, the problems faced include the low motivation of members to develop KWT and the lack of ability of members to manage KWT. In the financial aspect, the existing problems are limited capital owned and low ability in financial management. To overcome the above problems, several solutions are given including hydroponic training, business management training and training and assistance in business financial management. To overcome the lack of KWT cultivation equipment, in this program a grant is given in the form of cultivation equipment. The method of implementing this program is lecture, demonstration, practice and mentoring. The results of this activity are: KWT Anggrek has hydroponic growing media, KWT Anggrek members have knowledge and skills in hydroponic cultivation, and have an understanding of financial management.